Enhanced Solvatochromic Inversion in Cationic Stilbenes: Impact of π-extension on Their Solvent Polarity Sensitivity - Aliaga-Vidal, C; Aliaga-Vidal, C; Dominguez-Caru, M; Vidal-Palomo, M; Vidal-Palomo, M; Aburto-Bernal, I; Pastenes, C (Elsevier B.V., 2025)
Two series of cationic stilbenes with different length of their π-systems were synthesized and their spectral response in a wide range of solvent polarities exhibited inverted solvatochromism, with an inversion point occurring in mildly polar solvents. The addition of the 1,4-phenylene unit in the charge-transfer pathway of the dyes caused a notable shift in the solvent polarity at which the solvatochromic inversion point occurred. Quantum mechanics calculations corroborated the experimental findings, demonstrating charge transfer from the HOMO to the LUMO, with the 1,4-phenylene unit affecting orbital distribution. Multiparametric analysis indicated that these spectral behaviors are the result of a compensation of the sensitivity of the extended dyes to solvent acidity by solvent basicity, polarizability, and dipolarity. This study highlights the importance of π-extension in tuning the solvatochromic response of cationic dyes. © 2024 Elsevier B.V.